2006
DOI: 10.1152/ajpregu.00754.2005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and growth hormone stimulate somatostatin receptor (SSTR) expression by inducing transcription of SSTR mRNAs and by upregulating cell surface SSTRs

Abstract: This study examined the effects of insulin (INS) and growth hormone (GH) on mRNA and functional expression of somatostatin receptors (SSTRs). Rainbow trout liver was used as a model system to evaluate the direct effects of INS and GH on mRNA expression of three SSTR subtypes characterized previously from this species: SSTR1A, SSTR1B, and SSTR2. INS and GH directly stimulated steady-state levels of all SSTR mRNAs in a concentration- and time-dependent manner; however, the pattern of expression was hormone and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Responsiveness to SSA therapy is directly related to the receptor status of the tumor. Previously, studies using in vivo techniques or by using cell cultures in vitro have been reported [33,34,43,44]. Detection of SSTR is achieved by mRNA analysis using RT-PCR or in situ hybridization and protein level analysis using radioligand binding studies [29,32,34,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Responsiveness to SSA therapy is directly related to the receptor status of the tumor. Previously, studies using in vivo techniques or by using cell cultures in vitro have been reported [33,34,43,44]. Detection of SSTR is achieved by mRNA analysis using RT-PCR or in situ hybridization and protein level analysis using radioligand binding studies [29,32,34,44].…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide mainly binds to SSTR2 with high affinity and to SSTR5 and SSTR3 at about one-tenth of that affinity [28,30,43]. It is thought that the effects of octreotide depend on the SSTR subtypes expressed by that particular individual tumor.…”
Section: Percent Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternate forms of the SST-14 peptide containing a Pro2 residue (Pro2-SST-14) are derived from PPSST-2 [70]. Other forms of SST peptides are derived from PPSST-3 and PPSST-4 and have also been found in teleost fish [71,72]. All of these mature SST peptides are located at the C-terminal of SST precursors [72].…”
Section: Growth Hormone Inhibiting Hormone (Ghih or Somatostatin Sst)mentioning
confidence: 99%
“…Each SSTR associates with heterotrimeric guanine nucleotide-binding proteins (G-proteins) to mediate the inhibition of adenylyl cyclase activity, primarily, as well as mitogen-activated protein kinase and various phosphatases and ion channels [33,34]. Injury, cytokines, growth factors (including insulin and growth hormone, GH), and somatostatin itself regulate SSTR gene expression [35,36,37,38]. Initial responses of SSTR binding are diminished by continuous exposure via mechanisms of receptor desensitization, internalization, and degradation [35,39].…”
Section: Somatostatin Mechanisms Of Actionmentioning
confidence: 99%